1996
DOI: 10.1149/1.1836655
|View full text |Cite
|
Sign up to set email alerts
|

Thermal Nitridation of SiO2 Films in Ammonia: The Role of Hydrogen

Abstract: We investigated the transport of hydrogenous species during thermal nitridation of silicon dioxide films in ammonia by means of isotopic tracing of hydrogen. The dependence of the amount of hydrogen incorporated in the oxynitride films on the nitriding temperature and time, ammonia pressure, and on the initial oxide thickness was determined using methods that allow discrimination between the incorporation of hydrogen in the oxynitride films during nitridation and the effect of hydrogen adsorption during exposu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
39
0

Year Published

1997
1997
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(41 citation statements)
references
References 7 publications
2
39
0
Order By: Relevance
“…24 shows the energy locations of several defect centers in oxynitride, oxide, and nitride using numerical calculation [124]. Due to the fabrication methods, most of the defects in oxynitride are tied to the hydrogen and hydroxyl groups and are the major sources for hot-carrier induced related trap generation in nitrided oxide films [125][126][127][128]. Even in silicon oxide, it was shown that the neutral traps for electrons (r % 10 À17 cm 2 ) could be created due to the water diffusion into thermal oxide.…”
Section: Dielectric Trapsmentioning
confidence: 99%
“…24 shows the energy locations of several defect centers in oxynitride, oxide, and nitride using numerical calculation [124]. Due to the fabrication methods, most of the defects in oxynitride are tied to the hydrogen and hydroxyl groups and are the major sources for hot-carrier induced related trap generation in nitrided oxide films [125][126][127][128]. Even in silicon oxide, it was shown that the neutral traps for electrons (r % 10 À17 cm 2 ) could be created due to the water diffusion into thermal oxide.…”
Section: Dielectric Trapsmentioning
confidence: 99%
“…22 Ammonia begins to dissociate at 760 • C onto the silicon surface from where the reactive NH 2− , NH 2− , N 3− and H + species are able to interact and diffuse through the surface layer to create the silicon nitride film. 23,24 On the other hand, nitrogen does not begin to dissociate until substantial higher temperatures (> 1200 • C) and therefore is unable to interact with silicon substrate at lower temperatures. Ellipsometry reflectance measurement is a common and strong tool.…”
Section: Discussionmentioning
confidence: 99%
“…7-11, namely ͑i͒ growth of a SiO 2 film in O 2 , followed by nitridation in NH 3 , and then followed by reoxynitridation in N 2 O͑O 2 →NH 3 →N 2 O, samples 1-5 in Table I͒, [7][8][9] and ͑ii͒ growth of oxynitride films in N 2 O, followed by renitridation in NH 3 ͑N 2 O→NH 3 , samples 6-8͒. 10,11 Isotopically enriched gases were used for the RTP growth, namely, 99% 18 Table I, together with the total amounts of all isotopes present in the resulting oxynitride films as measured by nuclear reaction analyses ͑NRA͒. 12 Since the overall N concentrations in most of the films are rather moderate, their density can be taken as being approximately that of vitreous silica, giving the equivalent thickness relationship 10 15 ͑OϩN͒ atoms/cm 2 ϭ0.226 nm.…”
Section: © 1997 American Institute Of Physics ͓S0003-6951͑97͒03415-3͔mentioning
confidence: 99%
“…12 Since the overall N concentrations in most of the films are rather moderate, their density can be taken as being approximately that of vitreous silica, giving the equivalent thickness relationship 10 15 ͑OϩN͒ atoms/cm 2 ϭ0.226 nm. The 15 N and 18 O depth profiles were obtained by nuclear resonance profiling ͑NRP͒, using the strong, narrow, isolated resonances in the cross sections of the nuclear reactions 18 O͑p,␣) 15 N at 151 keV, and 15 N͑p,␣␥) 12 C at 429 keV, and a tilted sample geometry ͑⌿ϭ65°͒. 12-15 The measured excitation curves ͑i.e., ␣ or ␥ yields versus incident proton energy͒ around the resonance energy E R can be converted into concentration versus depth profiles by means of the SPACES simulation program.…”
Section: © 1997 American Institute Of Physics ͓S0003-6951͑97͒03415-3͔mentioning
confidence: 99%
See 1 more Smart Citation